PT BIO FARMA'S CSR GRASS RESOURCES RESILIENCE PROGRAM REVIEWED FROM THE SUSTAINABILITY COMPASS - Suwandi, Ariq Akmal; Humaedi, Sahadi (Indonesian Journal of Social Responsibility Review (IJSRR), 2024)
In implementing the company's CSR program, namely community development, it is not only about fulfilling regulations and formalities, but also providing benefits to the community recipients. Various kinds of improvements such as economic, capacity, welfare and sustainability must be accepted by the community because that is the aim of implementing community development carried out by the company. The method used in this research is descriptive qualitative to describe Sustainability in the Resilience Grass Resources (Re-Grass) program by CSR PT Bio Fama. The research aspect used by researchers uses the Sustainability Compass method which has 4 aspects, namely Nature, Economy, Society and Wellbeing, which is an analytical tool to invite the public to understand the sustainability of an activity that helps monitor the CSR program process. The research results show that the Resilience Grass Resources (Re-Grass) program by CSR PT Bio Fama which was given to the Bale Sawargi livestock group had a positive impact and experienced an increase in 4 aspects, namely Nature, Economy, Society and Wellbeing.